Distance Measure for Controlled Random Tests - V. N. Yarmolik; M. A. Shauchenka; V. V. Petrovskaya (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The problem of constructing characteristics of the difference between test sequences is investigated. Its relevance for generating controlled random tests and the complexity of finding difference measures for symbolic tests are substantiated. The limitations of using the Hamming and Damerau–Levenshtein distances to obtain a measure of the difference between test patterns are shown. For an arbitrary case, a new measure of the difference between two symbolic test sets is determined based on the interval used in the theory of the chain of successive events. The distance D(Ti, Tk) between test patterns Ti and Tk, using the interval characteristic, is based on determining independent pairs of identical (equal) symbols belonging to two patterns and calculating the intervals between them. The combinatorial nature of the calculation, the proposed difference measure for symbolic test patterns of an arbitrary alphabet and dimension, is shown. An example of calculating this measure is given and its possible modifications and limitations are shown. The application of the measure of difference is considered for the case of multi-run testing of memory devices based on address sequences pA with even p repetition of addresses. For the case p = 2, mathematical relations are given for calculating intervals and distances D(Ti, Tk) for address sequences 2A used for controlled random testing of memory devices. Experimental results are presented confirming the effectiveness of the proposed difference measure.